If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 12x = -11 Reorder the terms: 12x + 3y = -11 Solving 12x + 3y = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 12x + 3y + -3y = -11 + -3y Combine like terms: 3y + -3y = 0 12x + 0 = -11 + -3y 12x = -11 + -3y Divide each side by '12'. x = -0.9166666667 + -0.25y Simplifying x = -0.9166666667 + -0.25y
| 1.1x+1.2+-5.4=-10 | | 8k(4-6)-2x=16(3-k) | | 8(2x-3)-4=6x+9x-1 | | 30x-3x=X-2 | | 6x+15-7= | | 2(2n-1)=(n+3) | | 18+8x=9(x-2) | | 2(t-6)+6t=4(2t+3)-10 | | 3(9-3x)=45 | | x-5d=3 | | 6(-4x+5)=246 | | -77=7(1+4b) | | 4+3z-2=9z+9-7z | | 12+4(z-3)=3x+1 | | 5(r+3)-6=3(r-2) | | 3n+9=-3(2n+3) | | -28=7(7n-4) | | X^2=5*x^2-36 | | X+12+5x-17=2x+11 | | 7e^7t=11e^6t | | 5a+7b=17 | | 2(y+4)=21 | | 5*x^2-36-x^2=0 | | 3x-1=4x+9 | | x(x+3)-3=3x+1 | | 14-x=37 | | 7y-3=17 | | x^2+kx+8=k | | 5(m+4)-7= | | 5*x^2-x^2=36 | | 2(x^2-192)=0 | | .66d+1=16-d |